Genre Analysis in the Frame of Systemic Functional Linguistics - Najih Imtihani (Humaniora, 2010)
Systemic Functional Linguistics is a linguistics approach which cop-siders not only the structure of the language but also its social context. In the Systemic Functional Linguistics the concept of genre is defined as a step-by-step activity to reach the goal. The concept of genre is used to describe the cultural context in a language. According to this view, text should be seen and observed in its interaction with the context and social background. For that, the genre analysis will constantly involve the linguistic social context in the forms of field, tenor, mode, schematic structure and its realization in the text.